Implementation of Criminal Penalties Against Perpetrators of Sexual Violence - Viola Gemmy Gemaya; Henry Aspan; T. Riza Zarzani (International Journal of Synergy in Law, Criminal, and Justice, 2025)
The purpose of this paper is to determine how criminal penalties are applied to perpetrators of sexual violence and the main obstacles in implementing criminal penalties against perpetrators of sexual violence in the current legal system. The data collection technique used in this study is document study or library research, and the data analysis used in this study is qualitative analysis. Currently, there is a law regulating the Crime of Sexual Violence, namely Law Number 12 of 2022. The presence of this law is a hope for the community to reduce the growth of sexual violence cases that occur in Indonesia. Obstacles experienced include protracted legal processes (undue delay), evidence, the absence of articles regulating specific sexual crimes, intimidation from perpetrators, and lack of support from the victim's immediate environment.